Adherence to non-vitamin-K-antagonist oral anticoagulant medications based on the Pharmacy Quality Alliance measure. (2nd December 2015) - McHorney, Colleen A.; Crivera, Concetta; Laliberté, François; Nelson, Winnie W.; Germain, Guillaume; Bookhart, Brahim; Martin, Silas; Schein, Jeffrey; Lefebvre, Patrick; Deitelzweig, Steven
Abstract: Background: CMS Star Ratings help inform beneficiaries about the performance of health and drug plans. Medication adherence is currently weighted at nearly half of a Part D plan's Star Ratings. Including the adherence to non-vitamin-K-antagonist oral anticoagulants (NOACs) as a measure in the Star Ratings program may increase a plan's incentives to improve patient adherence. Objective: To assess the adherence to medication of patients who used the NOACs rivaroxaban, dabigatran, or apixaban in 2014 based on the Pharmacy Quality Alliance (PQA) adherence measure. Methods: Healthcare claims from the Humana database between July 2013 and December 2014 were analyzed. Adult patients with ≥2 dispensings of NOAC agents in 2014, at least 180 days apart, with >60 days of supply, and ≥180 days of continuous enrollment prior to the index NOAC were identified. The PQA measure was calculated as the percentage of patients who had a proportion of days covered (PDC) ≥0.8. Multivariate logistic regression analyses were also conducted adjusting for baseline confounders. Results: A total of 11, 095 rivaroxaban, 6548 dabigatran, and 3532 apixaban users were identified. Based on the PQA adherence measure (PDC ≥0.8), a significantly higher proportion of rivaroxaban users (72.7%) was found to be adherent compared to dabigatran (67.2%: p  < 0.001) and apixaban (69.5%: p  < 0.001) users. Compared to apixaban users, the adjusted likelihood of being adherent was significantly higher for rivaroxaban users (unadjusted OR [95% CI]: 1.17 [1.08–1.27], p  < 0.001; adjusted OR [95% CI]: 1.20 (1.10–1.31), p  < 0.001) and significantly lower for dabigatran users (unadjusted OR [95% CI]: 0.90 [0.82–0.98], p  = 0.019; adjusted OR [95% CI]: 0.85 [0.77–0.93], p  < 0.001). Limitations: Limitations of the study are potential inaccuracies in claims data, possible change in patterns over time, and the impossibility of knowing whether all supplied tablets were taken. Conclusion: Using the PQA's adherence measure, rivaroxaban users were found to have significantly higher adherence compared to apixaban and dabigatran users.